ASSESSMENT OF AIR QUALITY IMPROVEMENT POTENTIALS OF URBAN TREES IN KANO METROPOLIS, KANO STATE, NIGERIA - MOHAMMED A.,,; BUBA L. F.,,; KODIYA M. A.,; OLUWATOSIN O. L., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The study aimed at assessing air quality improvement potentials of urban trees in Kano Metropolis. Air pollutants considered include; CO, and CO2 . Temperature and relative humidity were also monitored. Sampling sites were identified and mapped out across the Metropolis using the ArcGIS software tool, the sampling sites where geo referenced using high sensitivity etrexgarmin GPS. Pollutant concentration and temperature were monitored using Air Quality kit in the sampling sites with many trees and sampling sites with few trees for a period of twice a day (morning and evening), three days a week for four weeks. Data were analyzed descriptively, while T test and ANOVA were carried out to determine if there is a significant difference between the sampling sites. The result obtained showed variations in the study area, where sites with many trees have lower concentration of pollutants and temperature than sites with few trees. The analysis indicated that there is a significant difference in the amount of air pollutant and temperature between sampling site with many trees and sites with few trees. This study has demonstrated that urban trees reduce the concentration of air pollutants and temperature in Kano Metropolis, thus improving urban air quality and consequently improve human health. The study recommends serious tree planting programme, review and enforcement of laws, harmonization and synergy between responsible authorities.